Pulmonary hypertension and echocardiogram parameters in obstructive sleep apnea - Wong, Hui Tong; Chee, Kok Han; Chong, Aun Wee (Springer, 2017)
Obstructive sleep apnea (OSA) is a growing health hazard in the United States and worldwide. OSA is now recognized as a disorder with systemic manifestations and its association with obesity and adverse cardiovascular consequences. There is increasing evidence that OSA may be associated with systemic hypertension and an increased incidence of stroke, heart failure, myocardial infarction, and arrhythmias. Less information is available about the association between OSA and pulmonary hypertension (PH). We therefore conduct this study to look at the prevalence of the pulmonary hypertension in obstructive sleep apnea patient and to identify risk factors leading to pulmonary hypertension among OSA patient. We studied and analyzed all OSA patient confirmed by polysomnograph in the year 2015. Twenty-five patients with OSA were included in this study with prevalence of pulmonary hypertension of 16%. Univariate analysis of various factors revealed a statistically significant association between having the lowest SpO2 of <70% and pulmonary hypertension (p = 0.016). There were no statistically significant associations between age, gender, smoking status, hypertension, body mass index (BMI), or apnea–hypopnea index (AHI) with occurrence of pulmonary hypertension. AHI is not a good predictor for pulmonary hypertension. The real value of using AHI to predict the health risk of OSA is doubtful. We recommend routine echocardiogram among OSA patient. The objective information in the echocardiogram provides evidence for counseling of patient with disease of OSA and hence hopefully can improve compliance of patient to treatment especially usage of CPAP.